Improving Elderly Knowledge and Readiness Through Community-Based Muscle Weakness Education: A Quasi-experimental Study - Agus Supinganto; Raufina Riandhani Mulyoto; Hamsu Kadriyan; Nuraini Staryo; Sumarmi Sumarmi; Dhea Natashia; Ni Ketut Metri; M. Syarif Hidayatullah; Suharmanto Suharmanto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Muscle weakness is an emerging public health concern among older adults worldwide, serving as a visible, primary symptom of sarcopenia. Sarcopenia is a complex geriatric syndrome characterized by progressive and generalized loss of skeletal muscle mass, strength, and physical function. However, awareness and knowledge regarding its prevention and management remain limited. This study aimed to evaluate the effectiveness of a community-based education program in improving knowledge and readiness among older adults to address muscle weakness. Methods: This study used a quasi-experimental, nonequivalent control group pretest-posttest design, conducted across six elderly schools in Mataram City and West Lombok, with 120 participants purposively recruited. Participants were divided into an intervention group (n = 60) and a control group (n = 60). The intervention group received two 60-minute multi-component muscle weakness education sessions comprising lectures, booklets, and interactive discussions, while the control group received no intervention. Knowledge and readiness were measured before and one week after the intervention using a validated questionnaire. To account for baseline imbalances and demographic confounding, data were analyzed using Analysis of Covariance (ANCOVA) with robust standard errors clustered at the school level. Results: At baseline, continuous questionnaire scores did not differ significantly between groups (p > 0.05). One week post-intervention, the intervention group's knowledge score increased from 11.23 ± 2.14 to 16.08 ± 1.45 (mean change: 4.85 ± 1.58; within-group d = 3.07), and readiness scores increased from 22.15 ± 4.12 to 29.43 ± 3.18 (mean change: 7.28 ± 3.35; within-group d = 2.18). The control group also showed increases, with a knowledge change of 2.87 ± 1.27 (d = 2.26) and a readiness change of 4.42 ± 4.46 (d = 0.99). Multivariable ANCOVA confirmed that the intervention was independently associated with significantly higher posttest knowledge (F(1, 115) = 24.32, p < 0.001, ?²p = 0.174) and readiness scores (F(1, 115) = 18.54, p < 0.001, ?²p = 0.139). Conclusion: A structured, multi-modal community-based educational intervention was associated with greater short-term improvement in knowledge and readiness scores compared to a control condition. This immediate questionnaire-based shift does not establish long-term clinical prevention or sustained behavior change. Integrating this program into community health services, such as Posyandu Lansia, represents a potential future direction warranting longitudinal evaluation of operational feasibility, behavioral retention, and objective physical outcomes.